Uniform Machine Gun Act, Act No. 80, §§ 1-14, 1935 Ark. Acts 171-75 - (:unkn) unknown (General Publisher, 1935)
Prohibited the possession of machine guns in crimes of violence, for offensive or aggressive purposes. The presence of a machine gun in any room, boat, or vehicle presumes ownership. Required registration of machine guns.
--
Keywords: MACHINE GUN RESTRICTION